2020
DOI: 10.1016/j.jhepr.2020.100168
|View full text |Cite
|
Sign up to set email alerts
|

The Fatty Liver Assessment in Germany (FLAG) cohort study identifies large heterogeneity in NAFLD care

Abstract: A German real world NAFLD cohort Standard of care intervention Highlights This is the first report on NAFLD from a secondarycare real-world cohort in Germany. In this outpatient cohort, diagnostics rely heavily on non-invasive surrogate scores and elastography to stage NAFLD. Every 10th patient presents with advanced fibrosis at baseline. Management of NAFLD in Germany consists predominantly of general lifestyle recommendations and best supportive care. The study underlines the applicability of noninvasive tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 40 publications
1
20
0
3
Order By: Relevance
“…Oeda et al analyzed 166 patients with biopsy-proven NAFLD 11 and found that approximately 25% of these patients fulfilled the histological criteria for progressive liver disease (NASH, NAS ≥ 4, and fibrosis score ≥ 2) 11 . Hofmann et al reported the characteristics and demographics of an observational NAFLD cohort in Germany 12 . In the subset using the FAST score (n = 107), 16.8%, 34.6%, and 48.6% of the patients were classified as rule in NASH, gray zone, and rule out NASH, respectively 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oeda et al analyzed 166 patients with biopsy-proven NAFLD 11 and found that approximately 25% of these patients fulfilled the histological criteria for progressive liver disease (NASH, NAS ≥ 4, and fibrosis score ≥ 2) 11 . Hofmann et al reported the characteristics and demographics of an observational NAFLD cohort in Germany 12 . In the subset using the FAST score (n = 107), 16.8%, 34.6%, and 48.6% of the patients were classified as rule in NASH, gray zone, and rule out NASH, respectively 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Hofmann et al reported the characteristics and demographics of an observational NAFLD cohort in Germany 12 . In the subset using the FAST score (n = 107), 16.8%, 34.6%, and 48.6% of the patients were classified as rule in NASH, gray zone, and rule out NASH, respectively 12 . Puri et al investigated 199 United States veterans; among them, 29%, 36.5%, and 36.5% were classified as rule in NASH, gray zone, and rule out NASH, respectively 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a qualitative study revealed low levels of patient education, support, and follow-up related to their diagnosis and implementation of lifestyle modification [59]. Poor understanding and inadequate support have been associated with low adherence to lifestyle modification programs among patients with NAFLD across Europe [78][79][80].…”
Section: Lifestyle Modification and Pharmacotherapeutic Management Of Nafld In Practicementioning
confidence: 99%
“…Overall, use of drugs otherwise indicated for the management of risk factors and that may improve liver pathology (e.g. metformin, glitazones, and statins), or other agent, including vitamin E, silymarin, phosphatidylcholine, and UDCA, was reported repeatedly: Asia [83], France [84], Germany [80], Poland [67], Romania [85], Russia [77] and the USA [86].…”
Section: Lifestyle Modification and Pharmacotherapeutic Management Of Nafld In Practicementioning
confidence: 99%
“…Einleitung/Epidemiologie Und Prognose Die Inzidenz und Prävalenz der nichtalkoholischen Fettleber (NAFLD) nimmt über die letzten Jahrzehnte weltweit rapide zu [1]. In Deutschland hat rund ein Viertel der Bevölkerung eine NAFLD [2], was eine zunehmende Belastung für das Gesundheitswesen darstellt. Somit ist die NAFLD in den letzten Jahren zur führenden chronischen Lebererkrankung in Deutschland avanciert.…”
Section: Introductionunclassified